Improving the precision and efficiency of the revenue contracts review by integrating a structured template and streamlined issue management - Masalunga, Reina Lyn (Animo Repository, 2023)
This action research aims to address the inefficiencies of the Revenue Contracts (RC) Review Process of Genesys’ APAC Revenue Team. Through meaningful collaborations, we identified that our unstructured RC review template and decentralized issue management were the main challenges we should target to improve our process’ precision and efficiency. We applied the Awareness, Desire, Knowledge, Ability, and Reinforcement (ADKAR) Framework to guide our transformation journey. In the first cycle of redesigning our RC review template, we discussed our inadequacies in our previous state. From there, we refreshed our knowledge of the ASC 606 and our company’s Revenue Policy to ensure accuracy in our proposed design. To streamline our Issue Management process, we targeted the most common issues identified through Root-Cause Analysis (RCA) and resolved these from the source systems. In doing so, we needed to communicate our observations and analysis to the involved parties outside our team and ask for their cooperation and commitment as we advocate for the initiative of this action research. In the second cycle, we encountered flaws and limitations in our proposed template that triggered us to revert to our original approach. This required us to revamp our RC review template to be more flexible and coherent. On the other hand, the Transformation Team willingly accepted and executed our Streamlined Issue Management project by re-engineering system logic that resulted in more precise revenue recognition, reduced RC issues, and improved overall revenue operations.